Diminishing Role of Young Manufacturing Plants as Drivers of Growth - Minho Kim (Korea Development Institute (KDI), 2018)
Korea's aggregate productivity growth in the manufacturing industry is on the decline, considerably influenced by the slowing productivity growth of young plants. A particularly sharp decline has been observed in the high-tech industry over the past three years. As such, government support programs need to aim at promoting growth and driving innovation and the numerous targets for support programs should be streamlined towards young innovative firms. The criteria for such firms should involve private sector investment in order to enhance the effectiveness of the programs. - Advanced countries are making renewed efforts to enhance innovation and competitiveness in manufacturing while concerns are growing in Korea over the industry's waning competitiveness. - This study analyzed the changes in the productivity growth of young manufacturing plants and proposed measures to improve the government's entrepreneurship support policy. - Young firms serve as a driving force for job creation and economic growth. - The share of young plants in the manufacturing industry has continued to decline, pointing to a weakening of Korea's economic dynamism. - The manufacturing industry's aggregate productivity growth has declined, particularly over the past three years. - Young plants account for nearly half of the aggregate productivity growth on average in manufacturing while their value-added share is only 13%. - The productivity growth of young plants has decreased over the past decade, diminishing its role as a growth engine. - The stagnating growth of young plants is a bigger factor to their declining productivity growth than the falling number of new entries. - The productivity growth of young plants in the high-tech industry, which has the highest R&D intensity, posted sharp decreases. - Industries with high R&D intensity have been the driving force behind the productivity growth of the manufacturing industry for two decades. But, the last three years have seen a steep decline in the productivity growth of the high-tech industry. - Although the average productivity of young plants is high, their contribution to aggregate productivity growth has declined due to their shrinking share of the industry. - While streamling the targets for the support programs towards innovative firms, the government should refrain from selecting and supporting firms directly and reform regulations that hinder entrepreneurship and the growth of innovative firms. - The government's verification process should be abolished and innovative firms should be defined as young venture capital firms or R&D firms. - Restructuring government programs should be based on objective project evaluations.
Keywords: 330